Economic Impact Assessment of Modern Technology of Legume Crops III Arid Rajasthan - Singh, B; Gajja, B L; Chand, Khem; Beniwal, R K (Annals of Arid Zone, 2016)
The impact of new technology to cultivate legume crop on productivity of moth bean and clusterbean was studied. Twenty-five farmers each adopting new and old technology were selected using simple random sampling technique. Total change in output due to improved technologies was 68 and 63% in moth bean and clusterbean, respectively. The contribution of improved variety (moth bean RMO-40 and clusterbean RSG 936) was 59% in moth bean and 42% in clusterbean. The remaining change in output was due to increased level of input use. The findings of the study have important implications for the arid regions of the state, since these crops occupy around 30% of the total cropped area.